Epitaxial growth of complex oxides on semiconductors - Posadas, Agham-Bayan S.; Ahn, Charles H.; ProQuest Dissertations and Thesis (Ann Arbor Yale University, 2007)
In combining two dissimilar materials in an epitaxial heterostructure, there are several major considerations that one must take into account in order to be successful. In this thesis, we study the integration of semiconductors with complex oxides. As demonstrations of how one should think about the epitaxial growth of complex oxides on semiconductors, we study two materials systems that highlight the major concerns that need to be addressed.
The first system is the hexagonal manganite YMnO3 on the wide bandgap semiconductor GaN grown by rf magnetron sputtering, where we observe behavior that makes sense only when chemical bonding at the interface is considered. We hypothesize a model of chemical bonding competing with elastic strain at the interface to explain the unexpected epitaxial relationship observed. Ferroelectric and magnetic measurements of the YMnO3 and YbMnO3 films show properties similar to bulk samples. The growth of YMnO3 on GaN also represents the first demonstration of the direct epitaxial growth of a functional complex oxide on a wide bandgap semiconductor.
The second system we studied is LaAlO3 on Si. In this system, in addition to chemical bonding, issues concerning thermodynamic stability and kinetics need to be addressed. By utilizing a thin SrTiO3 buffer, whose epitaxial growth on Si has already been demonstrated, as a transition layer for LaAlO3 growth, we demonstated for the first time the epitaxial growth of LaAlO3 on Si. Capacitance-voltage characteristics of the LaAlO3 samples show that epitaxial LaAlO3 on Si is a potential candidate material to replace SiO2 in Si-based field effect transistors.
Our demonstrations of successful complex oxide-on-semiconductor epitaxial growth of two different materials systems highlight the need to address not only lattice matching considerations but also chemical, thermodynamic, and kinetic concerns as well. Epitaxial growth of complex oxides on semiconductors allows for high quality functional films that can couple to the semiconductor for use in various applications, such as gate dielectrics. This work serves to highlight the need to take a broader view of all the different aspects of epitaxial growth in order to develop successful recipes for growing a complex oxide on a semiconductor.
Electronic reproduction.
Keywords: Condensation; Materials science